ESENSI PENGALAMAN BELAJAR MENYIMAK YANG INTERAKTIF: INTERPRETASI FENOMENOLOGIS ATAS PENERAPAN TPS DAN PODCAST DI SEKOLAH DASAR - Alkusnatun; Jeffry Handhika; Muh. Waskito Ardhi (CV Edujavare Publishing, 2026)
The development of listening skills in elementary school requires innovative and interactive strategies to overcome students' passivity. This study aims to interpret the essence of students' lived experiences in interactive listening learning through the implementation of the Think Pair Share (TPS) method and podcast media. This research uses a qualitative approach with a phenomenological design. Data were collected through in-depth interviews with six fifth-grade students and one teacher at SDN Nglandung 03, as well as participatory observation of the learning process. Data analysis followed the Stevick-Colaizzi-Keen method, involving horizontalization, thematization, and textural-structural description. The findings reveal three essential themes of the learning experience: (1) Podcast as an auditory stimulus that builds imagination and deep focus, (2) The